2002
DOI: 10.1023/a:1014535910946
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The male attractant pheromone of the scarab beetle Holotrichia reynaudi, an agricultural pest native to southern India, was extracted from abdominal glands of females with hexane and analyzed by gas chromatography-mass spectrometry. Field testing of the candidate chemicals, indole, phenol, and anisole, both alone and as binary mixtures, led us to conclude that anisole was the major component of the sex pheromone. Neither male nor female beetles were attracted to indole or phenol on their own. Similarly, when i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…To date, the organ responsible for sex pheromone production in the multicolored Asian lady beetle has yet to be elucidated. It is very likely that specific abdominal glands are involved in the production process, as observed for other Coleoptera species [41] , [42] and for the German cockroach, Blattela germanica L. [43] . Moreover, previous research on the eleven-spotted lady beetle, Semiadalia undecimnotata Schneider, demonstrated that glands with and without secretory ducts are distrubuted over the head, thorax, and abdomen.…”
Section: Discussionmentioning
confidence: 93%
“…To date, the organ responsible for sex pheromone production in the multicolored Asian lady beetle has yet to be elucidated. It is very likely that specific abdominal glands are involved in the production process, as observed for other Coleoptera species [41] , [42] and for the German cockroach, Blattela germanica L. [43] . Moreover, previous research on the eleven-spotted lady beetle, Semiadalia undecimnotata Schneider, demonstrated that glands with and without secretory ducts are distrubuted over the head, thorax, and abdomen.…”
Section: Discussionmentioning
confidence: 93%
“…Benzenoids including isoeugenol, methyl benzoate, anisole, veratrole, guaiacol, and phenol have been reported to play the role as deterrent to florivores, sex pheromones, fumigants for controlling pests, and aggregation pheromones [ 76 – 81 ]. For example, the anisole and phenol were documented to orientate scarab beetles as sex pheromones [ 80 , 82 , 83 ]. In addition, the anisole, veratrole, and guaiacol could effectively attract the Schistocerca gregaria as aggregation pheromones [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few reports have documented 4-methylanisole as an insect-derived sex pheromone or aggregation pheromone, but anisole, the homologue of 4-methylanisole, has been identified as the main component of the sex pheromone of the flower chafers Holotrichia reynaudi 3 , 41 and H. consanguinea 42 . In particular, anisole was used to capture a large number of female and male H. consanguinea , leading to aggregation and copulation behavior 6 , 42 .…”
Section: Discussionmentioning
confidence: 99%